Excitation Mechanism in Laser-Induced Plasma at Atmospheric Air Pressure - Jojor Lamsihar Manalu; Koo Hendrik Kurniawan; Tjung Jie Lie (Journal of Mathematical and Fundamental Sciences, 2005)
A special interferometric technique has been devised on the basis of rainbow refractometry without the use of an additional and delicate amplitude-splitting setup. This new technique was used for the characterization of plasma induced by a Q-switched Nd-YAG laser on zinc samples under atmospheric air pressure. An unmistakable signal of the density jump was detected simultaneously with the observation of the emission front signal. It was proved that the emission front and the front of the shock wave coincided and moved together with time at the initial stage of the secondary plasma expansion. However, at a later stage, the emission front began to separate from and left behind the shock wave front propagating in the surrounding air. With the use of zinc sample, the experimental results showed that the separation of the emission front and shock wave front took place at about 4 mm above sample surface for laser energy of 26 mJ. It was also found that the separation time increased by increasing the power density which further supported shock wave model. Analysis of the data of the shock front movement along with the emission characteristics has led us to the conclusion that models other than the shock wave model, such as the gas breakdown model, should be excluded, at least for a zinc sample, as not satisfactorily explaining the excitation process in the secondary plasma generated at atmospheric air pressure of 760 Torr.